What Collaborators Want: Planning, Monitoring and Evaluating Research Collaborations. (May 2017) - Fisher, N. I.; Peacock, A. J.
Abstract: This article describes an approach to planning, monitoring and evaluating research collaborations based on a structured approach to eliciting and measuring the value that each partner seeks to derive from the collaboration. During the phase of formulating the collaborative arrangements, the process can bring clarity to the initial expectations of each partner and so, possibly avoid prospective difficulties from the outset. During the course of the collaboration, it provides a means of assessing where improvements in the relationship might be needed. And at the end of the project, it provides a basis for assessing what has worked well, and what might need to be considered carefully in a future collaboration. The process also provides a basis for benchmarking collaborative ventures, based on ratings associated with the critical drivers of successful partnerships. Part of the process is studied in the context of the formation of a collaboration relating to cyber security research.